Investigating factors of pedestrian safety using ordinal logistic regression in Addis Ababa City roads - Bishaw, Temesgen Walelign; Nurye, Gebrechiristos; Singh, Ranavijai Bahadur (Frontiers in Sustainable Cities, 2024)
Pedestrians are the most victimized group in traffic accidents, and this has raised concerns about pedestrian safety in urban Ethiopia. The aim of this study is to determine the factors that affect pedestrian safety in Addis Ababa city Roads. This study employed a concurrent mixed-methods research method and an explanatory research design. Perception-based pedestrian safety data was collected from respondents’ key informants and personal observation. Exploratory factor analysis was employed to identify significant variables. Besides, the fitness of each variable was evaluated under the assumption of ordinal logistic regression, and the effect size of significant variables was determined using the odds ratio. The result indicates pedestrians are 0.065, 0.181, 0.296, 0.324, 0.289, 0.306, 0.038, and 0.193 times less likely to be safe due to narrow sidewalk width, poor sidewalk and footpath pavement comfort, inclusivity problems of sidewalks and footpaths, illegal vehicle parking, street vending, fast vehicle speed, and absence of traffic signs and lights, respectively. Consequently, the use of ordinal logistic regression offers a practical and effective means of determining pedestrian safety factors. Better pedestrian facilities should be constructed by considering pedestrian flow and diversity. Besides, the concerned body should provide spaces for street vendors and car parking and enforce traffic rules in the appropriate system to control vehicle speed.